A patient survey on outpatient physiotherapy services in Nepal: service received, and patients’ recommendations - Nishchal Ratna Shakya; Nistha Shrestha; Gillian Webb; Hellen Myezwa; Biraj Man Karmacharya; Ann-Katrin Stensdotter (BMC Health Services Research)
Abstract Background A global rising burden of non-communicable diseases and disability increases the need of and demand on physiotherapy. In Nepal, knowledge is lacking about provision and utilisation of physiotherapy. This study aimed to explore patients’ perception about physiotherapy and the service received at their outpatient physiotherapy clinic. The rationale was to understand the needs and identify areas of potential improvement in service delivery. Methods A cross-sectional survey with closed and open-ended questions was performed in the Bagmati province of Nepal at 29 health-centres of 6 districts including 20 patients per facility (n = 580). Descriptive and regression analysis were performed for closed ended questions and thematic content analysis used for the open-ended questions. Results Among patients receiving physiotherapy, 55.3% were females and 48.1% belonged to the upper caste or advantaged ethnic groups, 76.4% were referred by doctors and 76.6% were paying out of pocket. Musculoskeletal (80.7%) and neurological (29.1%) conditions were most common with some comorbidity. The most frequent interventions were electrotherapy and resistance training (≈ 65%). Accessibility was explained by educational level, urban / rural area and travel time. Affordability was explained by age, mode of payment and treatment duration. Age, educational level, and mode of payment likewise explained satisfaction. Patients’ recommendations for improving physiotherapy were clustered on nine: satisfaction, availability, equipment, awareness, service improvement, human resources, affordability, adequate space and proper counselling. Conclusion Based on the findings, Nepal should target political priorities including infrastructure, quality system for evidenced practice and clinical conduct, rural development and availability for the poor.